2013
DOI: 10.1038/jid.2012.250
|View full text |Cite
|
Sign up to set email alerts
|

Aloxe3 Knockout Mice Reveal a Function of Epidermal Lipoxygenase-3 as Hepoxilin Synthase and Its Pivotal Role in Barrier Formation

Abstract: Loss-of-function mutations in the lipoxygenase (LOX) genes ALOX12B and ALOXE3 are the second most common cause of autosomal recessive congenital ichthyosis. The encoded proteins, 12R-LOX and epidermal LOX-3 (eLOX-3), act in sequence to convert fatty acid substrates via R-hydroperoxides to specific epoxyalcohol derivatives and have been proposed to operate in the same metabolic pathway during epidermal barrier formation. Here, we show that eLOX-3 deficiency in mice results in early postnatal death, associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
131
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(137 citation statements)
references
References 31 publications
4
131
0
2
Order By: Relevance
“…Similarly, the distances between C 10 and the iron bound hydroxyl [d(C 10 -OH)] vary between 3.28 to 3.67 Å (SI Appendix, Table S5). For structures XI to XX, which represent arachidonic acid conformers for 15-lipoxygenation, C 13 is also located at reactive distances (SI Appendix, Table S5). These data indicate that, if one considers only the geometric distances, hydrogen abstraction from both C 10 and C 13 is possible.…”
Section: Simulations and Quantum Mechanics/molecular Mechanicsmentioning
confidence: 99%
“…Similarly, the distances between C 10 and the iron bound hydroxyl [d(C 10 -OH)] vary between 3.28 to 3.67 Å (SI Appendix, Table S5). For structures XI to XX, which represent arachidonic acid conformers for 15-lipoxygenation, C 13 is also located at reactive distances (SI Appendix, Table S5). These data indicate that, if one considers only the geometric distances, hydrogen abstraction from both C 10 and C 13 is possible.…”
Section: Simulations and Quantum Mechanics/molecular Mechanicsmentioning
confidence: 99%
“…Furthermore, recent findings have demonstrated that ALOX12B and ALOXE3 are involved in the reactions necessary for conversion of acylceramide to proteinbound ceramide, i.e., peroxidation of the linoleate moiety and subsequent epoxyalcohol derivatization (13). In addition, ALOX12B was proven not to be involved in hepoxilin/trioxilin production (30). These findings suggest that, although hepoxilin/ trioxilin metabolism may not be relevant to the pathogenesis of ichthyosis, the impairment of acylceramide/protein-bound ceramide formation causes ichthyosis.…”
Section: Discussionmentioning
confidence: 68%
“…Alterations in Alox12b expression were shown to be often associated with the defective skin barrier functions subsequently resulting in epidermal hyper-proliferation [19,27]. CLDN1 was shown to act as a signal mediator to regulate gene expression and cell migration in human oral and lung cancer cells [11,28].…”
Section: Discussionmentioning
confidence: 99%
“…Arachidonate 12R-lipoxygenase (Alox12b) shown to be involved in mouse epidermal differentiation and skin barrier formation is induced in epidermoid carcinomas contributing to the tumor cell proliferation [18]. Genetic inactivation of Alox12b leads to thickening of the epidermis, hyper-proliferation of epidermal cells, and severe hyperkeratosis in mice [19], while the ALOX12B inhibition enhances human tumor cell death [20].…”
Section: Introductionmentioning
confidence: 99%